Power and discourse in the politics of evidence in sport for development. Issue 2 (April 2016) - Harris, Kevin; Adams, Andrew
Highlights: Power dynamics that shape evidence in sport for development are analysed. Discourses relating to SFD processes are examined through a foucauldian lens. This addresses what is power and whose interests are served in the reporting of evidence? The sport practitioner is underprivileged and needs to be better understood Abstract: The field of sport for development (SFD) has been criticised for the way that evidence has been produced and used to account for and demonstrate the perceived success of SFD programmes. Much of this critique has highlighted shortcomings in approaches to monitoring and evaluation (M&E), which underpins a perceived weak evidence base concerning what works, why and within which contexts (Coalter, 2007; Coalter & Taylor, 2010; Pawson & Tilley, 1997 ). Conceptually a lack of evidence discourse (Nicholls et al., 2010 ) has emerged. This paper explores and analyses the power dynamics that shape this discourse and argues that an understanding of the dominant neoliberal context within which SFD is located is critical. While offering a Foucauldian framework, the power, knowledge and discourse related to political actors in SFD processes are examined. This paper addresses two key questions: what is power and who is it for? Whose interests are served in the interpretation, generation and reporting of evidence? The paper concludes that the role of the sport development practitioner (SDP) is underprivileged and to enable the field of sport for development (SFD) to move forward, the very people who implement the programmes need to be better understood. Furthermore it is argued that a deeper understanding and interpretation of the terrain of the sport development practitioner (SDP) within UK and international shores are a necessity if a more open and transparent knowledge transfer process, surrounding evidence, is to be entered into.